Penyuluhan Pemanfaatan Limbah Cair Tapioka Sebagai Alternatif Pembuatan Nata De Cassava Di Kelompok PKK Desa Krawang Sari, Natar, Lampung Selatan - Hardoko Insan Qudus; Endang Nurcahyani; Tundjung Tripeni Handayani; Sri Wahyuningsih; Sutyarso (CV. Multi Kreasi Media, 2023)
The tubers of cassava or cassava (Manihot esculenta Crantz) are widely known as a staple food that produces carbohydrates and the leaves are a vegetable. Indonesia is the second largest cassava producing country after Nigeria with a five-year average total supply of 9.67 million tons. Processed cassava produces two-thirds of the by-products of its raw materials in the form of tapioca cob, skin, and liquid waste. Tapioca liquid waste can pollute the surrounding environment because it produces an unpleasant odor. Based on these reasons, it is necessary to develop new innovations in their utilization, which so far have not been utilized by the community. This new innovation is to use liquid tapioca waste to make Nata de Cassava which is a high fiber and nutritious food. The aim of the service is to provide knowledge to the women of the “PKK” group in Krawang Sari Village, Natar, South Lampung in making Nata de Cassava from liquid tapioca waste. The result of this service activity is that there is an increase in participants' knowledge about how to use liquid tapioca waste to make Nata de Cassava, which can be seen from the average increase in participants' knowledge of 33.33 points and the percentage increase in knowledge of 61.33%.